2015
DOI: 10.1002/dev.21377
|View full text |Cite
|
Sign up to set email alerts
|

Infant and adult pupil dilation in response to unexpected sounds

Abstract: Surprisingly occurring sounds outside the focus of attention can involuntarily capture attention. This study focuses on the impact of deviant sounds on the pupil size as a marker of auditory involuntary attention in infants. We presented an oddball paradigm including four types of deviant sounds within a sequence of repeated standard sounds to 14-month-old infants and to adults. Environmental and noise deviant sounds elicited a strong pupil dilation response (PDR) in both age groups. In contrast, moderate freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
118
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(133 citation statements)
references
References 86 publications
11
118
0
Order By: Relevance
“…Environmental sounds have a complex structure since they contain a variety of frequencies, whereas pitch-deviant sounds contain only a single frequency. Even infants processed physically complex oddball sounds (e.g., bursts of noise) differently from pitch-deviant sounds (Wetzel et al, 2016). In their auditory-visual oddball study, the distractor-related pupil dilation response was clearly increased in response to noise oddball sounds (that included a variety of frequencies), whereas no response was observed in response to pitch-deviant sine wave sounds (included a single frequency).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental sounds have a complex structure since they contain a variety of frequencies, whereas pitch-deviant sounds contain only a single frequency. Even infants processed physically complex oddball sounds (e.g., bursts of noise) differently from pitch-deviant sounds (Wetzel et al, 2016). In their auditory-visual oddball study, the distractor-related pupil dilation response was clearly increased in response to noise oddball sounds (that included a variety of frequencies), whereas no response was observed in response to pitch-deviant sine wave sounds (included a single frequency).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the sound of the one's own smartphone captures more attention than the sounds of other smartphones when presented in an oddball paradigm to adults (Roye et al, 2007). Even infants responded to oddball sounds, that provided an emotional meaning (e.g., the cry of a peer), with increased pupil dilation than in response to a phone ring which had a similar complexity but a probably less significant meaning (Wetzel et al, 2016). Semantic information therefore might increase the personal significance of novel sounds contributing to differences between the conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Pupil dilation is governed both sympathetically and parasympathetically (Steinhauer, Siegle, Condray, & Pless, 2004), with parasympathetic arousal causing constriction and sympathetic arousal causing dilation. Although this means that a dilatory response may result from either arousal of the SNS or inhibition of the PNS (Bradley, Sapigao, & Lang, 2017), due to the slightly different time scales on which these two systems may operate, these contributions may be dissociable in the pupillary response signal through statistical means (Wetzel, Buttelmann, Schieler, & Widmann, 2016;Widmann, Schröger, & Wetzel, 2017). Although the following hypothesis is still highly speculative at the moment, we suggest that this may be significant because, although both cognitive and affective (emotional) stimulation may result in pupil dilation, emotionally evocative stimuli appear to cause pupil dilation primarily through sympathetic arousal (Bradley et al, 2017), while cognitive demand induces primarily parasympathetic withdrawal (Steinhauer et al, 2004).…”
Section: Pupil Dilationmentioning
confidence: 99%
“…These research questions might be answered using neurophysiological and psychophysiological approaches. For example, a recent study demonstrated that pupillometry can be used to study distractor processing in preverbal children (Wetzel, Buttelmann, Schieler, & Widmann, 2016).…”
Section: Limitationsmentioning
confidence: 99%